MANAGEMENT OF LATENT TUBERCULOSIS INFECTION BASED ON T-SPOT.TB ASSAY IN PATIENTS WITH HEMATOLOGICAL MALIGNANCIES - Emrah Kiliacaslan; Kadir Canoglu (Mediterranean Journal of Hematology and Infectious Diseases, 2022)
Background and objective: Patients with latent tuberculosis infection (LTBI) receiving chemotherapy for hematological malignancy (HM) are at high risk of developing active tuberculosis (TB) infection. The aim of this study is to show real-life data and results of the T-SPOT test and preventive isoniazid (INH) therapy in pre-chemotherapy LTBI screening in the HM patient group.